The Influence of Product Quality and Price on Consumer Satisfaction in the Jdm Project Printing Business - Fera Kusumawati; Hartono; Rini Armin (International Journal of Management and Business Economics, 2023)
This study aims to determine the effect of product quality and price on customer satisfaction in the JDM PROJECT printing business. This study used a quantitative method with a total sample of 96 respondents using incidental sampling technique. The data collection method uses an online questionnaire. This study uses multiple linear regression analysis with data processing tools in the form of the IBM SPSS 21 program. The results show that product quality partially affects consumer satisfaction (Sig 0.000 <0.05, and t count 3.056 > t table 1.989) and price partially affect consumer satisfaction (sig 0.000 <0.05 and t count 6.192 > t table 1.989). Product quality and price simultaneously affect consumer satisfaction in the JDM PROJECT printing business (sig 0.000 <0.05 and f count 22.075 > f table 3.09).